Thioctamer: a novel thioctic acid–glatiramer acetate nanoconjugate expedites wound healing in diabetic rats. (31st December 2022) - Alhakamy, Nabil A.; Mohamed, Gamal A.; Fahmy, Usama A.; Eid, Basma G.; Al-Rabia, Mohammed W.; Khedr, Amgad I. M.; Nasrullah, Mohammed Z.; Ibrahim, Sabrin R. M.; Abdel-Naim, Ashraf B.; Ahmed, Osama A. A.; Md, Shadab
Abstract: The current work aims to design thioctic acid (TA) and glatiramer acetate (GA) nanoconjugate (thioctamer) loaded hydrogel formula as well as evaluation of thioctamer preclinical efficacy in expediting wound healing in a rat model of the diabetic wound. Thioctamer was prepared by conjugation of GA and TA in a 1:1 molar ratio. Particle size, zeta potential, and thermodynamic stability of the prepared thioctamer were assessed. Thioctamer was loaded in hydroxypropyl methylcellulose-based hydrogel and in vitro release study was investigated. The ability of thioctamer to enhance the process of wound healing in diabetic rats was investigated by assessing wound contraction and immunohistochemical assessment of the inflammation markers IL-6 and TNF-α. The results demonstrated that thioctamer showed particle size of 137 ± 21.4 nm, polydispersity index (PDI) of 0.235, and positive zeta potential value of 7.43 ± 4.95 mV. On day 7 of making a skin excision, diabetic rat wounds administered thioctamer preparation showed almost complete healing (95.6 ± 8.6%). Meanwhile, % of wound contraction in animals treated with TA or GA groups exhibited values amounting to 56.5 ± 5.8% and 62.6 ± 7.1%, respectively. Histological investigation showed that the highest healing rate was noted in the thioctamer group animals, as the surface of the wound was nearly fully protected by regenerated epithelium with keratinization, with few inflammatory cells noticed. Thioctamer significantly ( p <.05) inhibited IL-6 and TNF-α expression as compared with sections obtained from the negative control, TA, GA, or positive control group animals on day 7. The evidence of the ability of thioctamer to significantly expedite wound healing in the diabetic rats is presented.